2015
DOI: 10.1111/brv.12219
|View full text |Cite|
|
Sign up to set email alerts
|

Use of erythrocyte indicators of health and condition in vertebrate ecophysiology: a review and appraisal

Abstract: We review evidence for and against the use of erythrocyte indicators of health status and condition, parasite infection level and physiological stress in free-living vertebrates. The use of indicators that are measured directly from the blood, such as haemoglobin concentration, haematocrit and erythrocyte sedimentation rate, and parameters that are calculated from multiple measured metrics, such as mean cell volume, mean cell haemoglobin content or mean cell haemoglobin concentration is evaluated. The evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 151 publications
2
52
0
Order By: Relevance
“…Data on the effects of blood parasites on the level of haemoglobin in nestlings are consistent for different study species and indicate negative effects of parasitism on the haematological condition of chicks and adult birds (Johnstone et al 2015;Minias 2015). Krams et al (2013) showed experimentally that in the absence of blood parasites, Great Tit nestlings had higher concentrations of haemoglobin.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Data on the effects of blood parasites on the level of haemoglobin in nestlings are consistent for different study species and indicate negative effects of parasitism on the haematological condition of chicks and adult birds (Johnstone et al 2015;Minias 2015). Krams et al (2013) showed experimentally that in the absence of blood parasites, Great Tit nestlings had higher concentrations of haemoglobin.…”
Section: Discussionmentioning
confidence: 57%
“…The concentration of haemoglobin was shown to be a relatively simple biochemical indicator of bird metabolism and condition (Sergent et al 2004;Simmons and Lill 2006;Minias 2015;Johnstone et al 2015). It reflects the presence of pathogens and parasites, as well as the nutritional status of organism (a drop in haemoglobin concentration suggests nutritional deficiency ;Campbell 1995;Simon et al 2004;Kasprzyk et al 2006;Słomczyński et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a positive association between haematocrit and condition is generally assumed. However, regenerative anaemia occurs when individuals respond to reductions in RBC or haemoglobin concentrations by stimulating the release of immature RBCs from bone marrow and/or increasing the generation of RBCs (erythropoiesis), leading to an increase in haematocrit (Johnstone, Lill, & Reina, 2017; Teague et al, 2007). Thus, over intermediate time‐scales (days–weeks), frequent or prolonged exposure to stressors can increase haematocrit.…”
Section: Methodsmentioning
confidence: 99%
“…We considered five broad categories of explanatory variables thought to influence the overall condition of birds in agricultural landscapes, including farm and landscape features of interest and potential confounding factors, such as climate, age, sex, season and time of day (Ellis et al, 2012; Johnstone et al, 2017; Table 1).…”
Section: Methodsmentioning
confidence: 99%